Lower the Flag: A Qualitative Analysis of Behavioral Alerts in the Electronic Health Record - Zoë Kopp; Irina Kryzhanovskaya; Maria E. Garcia (Health Equity)
Background: Behavioral alerts (BAs) are electronic health record communication tools used to notify clinicians and staff about patient behavioral incidents. Despite their widespread presence, limited research exists on the content and use of BAs. Methods: This study took place in a large, urban, academic general internal medicine practice. Demographics of patients with BAs were compared with all patients at the practice (N = 27,023). Only patients with active BAs (N = 518) were included in the qualitative analysis. Themes were generated through open and axial coding of BAs’ free-text and thematic analysis to describe the content of BAs. Results: A total of 518 patients in the practice had BAs (1.9%). Compared with the general practice population, patients with BAs were more likely to be Black (23% vs. 8.5%), have public insurance (77.8% vs. 41.9%), and have a psychiatric (62.5% vs. 30.7%) or substance use-related (36.1% vs. 5.8%) diagnosis. We identified six BA themes: criminalization (behavior described as criminal or necessitating law enforcement), implied overuse (exploitation of medical resources with recommendation for limitation), advocacy (author offers support and defense), coordinating care (logistic details), venting (expression of negativity without a plan), and warning (communication of risk). Discussion: The wide-ranging content of BAs demonstrates their varied, unstandardized use. The unregulated use of BAs should be reexamined and restructured to avoid negatively impacting patients, particularly given their disproportionate use for historically marginalized populations, including patients who are Black, have public insurance, and those with psychiatric or substance use-related diagnoses.